(untitled) (Nuntius Antiquus, 2010)
The few remaining fragments from the works of the Latin poet Cornelius Gallus (c. 70-26 BC), discovered in Egypt in 1978, are presented, translated and analyzed in this paper. The role of these works among the books dated from the time of the poet, as well as some critical appreciation left by poets that lived during the Augustan reign and elected Cornelius Gallus as a model, are also brought into discussion. In addition, a poetic translation is also suggested.